(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The influence of heat treatment during curing process of ultra high strength concrete (UHSC) was researched. Four different heat treatment temperatures ranging from 50 to 200 °C were studied and compared to the reference temperature regime (20 °C). Two series of heat treatment were applied: (a) at the early age of UHSC (3 days) and (b) after 27 days of standard curing regime in water at 20 °C. Concrete compressive strength was tested at the early age (4 days) and at the age of 28 days. The water absorption and water penetration under pressure were tested for heat treated and untreated UHSC specimens. SEM and XRD investigations of the studied samples were performed. UHSC with the strength of 123 MPa at the age of 28 days was tested at the standard curing conditions. Results indicate that early age curing at elevated temperature increases early compressive strength from 123 to 189% while at the age of 28 days the compressive strength was only 95 to 117% from reference and depends on the heat treatment regime. The heat treatment of UHSC at the age of 27 days was beneficial with regard to the strength development. Heat-treated UHSC provided compressive strength gain from 112 to 124% from reference. The water absorption for all UHSC specimens was from 2.6 to 3.2 wt.% and it was not affected by the heat treatment. The calcite was detected with XRD in heat treated UHSC samples which indicates the carbonization of Portlandite. This could explain the strength gain of heat-treated samples and the reason for slow compressive strength increase in the case of early heat treatment application. SEM images reveal dense structure and unreacted silica fume particles. The early heat treatment initiated high early strength but the strength of concrete reduced at the age of 28 days comparing to the early strength; therefore late heat application was beneficial for strength gain of the UHSC.